Pengaruh Tata Kelola Pemerintah Daerah Terhadap Transparansi Pengelolaan Keuangan Daerah: Bukti Empiris Pada Pemerintah Provinsidi Indonesia - Syamsul Syamsul; Irwan Taufiq Ritonga (Jurnal Akuntansi, 2017)
This study developed a research Beekes and Brown (2006) who found that corporate governance makes companies more informative (more transparent). This study aims to prove whether the same results were also found in environmental governance in Indonesia. The theory is used to achieve the goal of this research is the theory of agency. This research was conducted in 32 local governments in Indonesia. Based on a simple regression model, this study shows that local governance affects positively the transparency of local financial management. Such findings reinforce previous research. The findings of this study provide a useful contribution to government officials (executive and legislative), in demonstrating the important role of local governance in encouraging the transparency of local financial management. In addition, the findings of this study can be used as the basis for further research related to the topic of local governance and transparency of local financial management.